Working towards Usable Forms on the Worldwide Web: Optimizing Multiple Selection Interface Elements. (24th May 2011) - Bargas-Avila, Javier A.; Brenzikofer, Olivia; Tuch, Alexandre N.; Roth, Sandra P.; Opwis, Klaus
Abstract : If an interactive form in the worldwide web requires users to select multiple answers from a given list, this can be implemented in several ways. This paper discusses an empirical study withn = 106 participants, where two interface elements for choosing multiple answers (checkboxes and list boxes) were compared. Results showed that participants chose the same amount of options in both conditions but were faster and more satisfied using checkboxes. The time differences disappeared after several trials, revealing a learning effect for the list box element. As a conclusion, it can be recommended that website developers and online researchers should use checkboxes instead of list boxes for their online forms and questionnaires to enhance usability and user satisfaction—at least for a smaller number of options.